2003
DOI: 10.1001/archpsyc.60.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Once-a-Day Formulation of Methylphenidate for the Treatment of Attention-deficit/Hyperactivity Disorder

Abstract: These studies demonstrate the translation of a basic science finding (acute tolerance to clinical doses of methylphenidate) into clinical application (the selection of a new drug delivery pattern for methylphenidate). This approach produced a new product (OROS-methylphenidate or Concerta), which proved to have the predicted rapid onset (with 1-2 hours) and long duration of efficacy (10-12 hours) after a single administration in the morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
143
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 21 publications
5
143
0
11
Order By: Relevance
“…As expected and documented in the research literature (Pelham et al 2001;Swanson et al 2003), the primary efficacy endpoints that the PERMP and SKAMP measured at 4 hours were statistically significant for the comparison between OROS MPH and placebo. These results demonstrate improvement in classroom behaviors, productivity, attention to task, and other core symptoms of ADHD with OROS MPH.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As expected and documented in the research literature (Pelham et al 2001;Swanson et al 2003), the primary efficacy endpoints that the PERMP and SKAMP measured at 4 hours were statistically significant for the comparison between OROS MPH and placebo. These results demonstrate improvement in classroom behaviors, productivity, attention to task, and other core symptoms of ADHD with OROS MPH.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the large number of efficacy measures included in this study, investigators scheduled exploratory assessments during the time period when maximum drug effects would be expected based on previously conducted pharmacodynamic and pharmacokinetic studies (Pelham et al 2001;Swanson et al 2003). During the laboratory school day, there was also a need to balance the large number of academic measurements in this study with other components of the day, including meals and fun/recess activities, within a prolonged evaluation day in a young age group.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Controlled-release MPH delivers methylphenidate via an osmotic pump to produce a smooth, ascending profile with duration of treatment effect through 12 hours. 15 Once-daily dosing of controlled-release MPH at 8 am is equivalent to thrice-daily MPH dosed at 8 am, 12 pm, and 4 pm. In this crossover design study, driving performance of ADHD-diagnosed adolescents (age range, 16 to 18 years) was assessed using a sophisticated driving simulator at 2 pm, 5 pm, 8 pm, and 11 pm Driving performance worsened by a factor of 5 at 8 pm and 11 pm when subjects received IR MPH.…”
mentioning
confidence: 99%
“…Earlier studies have demonstrated the onset of action of OROS methylphenidate to be 1 hour post dose, with length of activity of no more than 12 hours [8][9][10][11] . The time to peak plasma concentration has been found to be 6.8±1.8 hours.…”
Section: Discussionmentioning
confidence: 99%